2017
DOI: 10.1016/j.pvr.2016.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparative accuracy of Pap smear and HPV screening in Ubon Ratchathani in Thailand

Abstract: We evaluate the potential for using high-risk human papillomavirus (hr-HPV) testing-based screening for cervical intraepithelial neoplasia (CIN) in routine health services in Thailand; its accuracy in comparison to that of conventional cytology (CC); and the utility of HPV16/18 positive results and liquid-based cytology (LBC) triage for HPV-positive women in the detection of high-grade CIN. Women aged 30–60 years in Ubon Ratchathani province, Thailand were screened with CC and hr-HPV testing and those abnormal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…However, the use of human papillomavirus (HPV) DNA test as a screening method has been considered more helpful for protection against invasive cervical carcinomas in some studies [5]. The HPV DNA test has also been suggested as a screening method in some countries [6][7][8].…”
mentioning
confidence: 99%
“…However, the use of human papillomavirus (HPV) DNA test as a screening method has been considered more helpful for protection against invasive cervical carcinomas in some studies [5]. The HPV DNA test has also been suggested as a screening method in some countries [6][7][8].…”
mentioning
confidence: 99%
“…It is reported that the hrHPV test is superior to cytology for the early detection of high-grade cervical epithelial lesions (Cuzick et al, 2008). Our pilot study in Ubon Ratchathani demonstration the feasibility of integrating HPV testing into public health services in Thailand (Sangrajrang et al, 2017). In addition, cost-effectiveness analysis provided support for full implementation of HPV testing as the primary method for cervical screening in Thailand (Termrungruanglert et al, 2017).…”
Section: Cervical Cancermentioning
confidence: 70%
“…26 Another investigator found only 0.4% of women to be ASCUS positive on Pap smear. 17 There was a significant association between the duration of having anogenital warts and the inflammatory cells infiltration and ASCUS. The more severe inflammatory reaction was in those patients having warts for months.…”
Section: Discussionmentioning
confidence: 93%
“…Our results are consistent with a Turkish study in which over ninety percent of the study group had never heard of and had not undergone Pap smear screening before, 16 while others reported that 95.3% of women had prior screening with Pap smear. 17 This lack of screening in our area will increase the risk of late diagnosis and invasive cervical cancer. Pap smears taken in the mass-screening program have a larger effect on invasive cervical carcinoma.…”
Section: Discussionmentioning
confidence: 99%